ANALISIS PERBANDINGAN KINERJA KEUANGAN BANK RAKYAT INDONESIA (PERSERO) TBK (SEBELUM DAN SESUDAH DILUNCURKAN SATELIT BRISat) - Nurhayani Lubis; Hardi Hardi; Sri Maryanti (Jurnal Ilmiah Ekonomi Dan Bisnis, 2023)
This research was conducted to see how the company's financial condition before and after the launch of the satellite. Where for Bank Rakyat Indonesia, Tbk, one of the strategies used is to invest in technology, namely by launching a satellite called BRIsat. With the launch of BRISat, it can help BRI in providing the best service. And also by having its own satellite, BRI can expand its service coverage to remote areas and maximize services. In its development, of course, it is hoped that there will be differences in the company's performance before and after the launch of the satellite. From the results of testing 9 hypotheses using SPSS, only 4 hypothesis tests were accepted. Namely on the variables ROE, BOPO, CAR, and DER. The other variables are QR, LDR, LAR, ROA, and NPM variables whose test results are not accepted. So it can be concluded as a whole that BRI's technology investment through BRISat has the most influence on bank management in managing capital, the efficiency of a bank's management performance and bank distribution in carrying out its operational activities, affects the adequacy of a bank's capital, and affects debt and equity.